Legal Certainty of Income Tax Imposition on Sale and Purchase Transactions of Uncertified Land - Nursyafitri, Dwi; Sudiro, Amad (Universitas Sriwijaya, 2024)
In the land registration process, there are tax payment obligations that must be carried out by the parties, both sellers and buyers, before obtaining a certificate issued by the Land Office. Final Income Tax on Transfer of Land and Building Rights (PPh F PHTB) is an obligation that must be paid by the landowner. In the case of uncertified land, PPh F PHTB is imposed on the landowner twice. In addition, the landowner is also charged a one-time Land and Building Acquisition Fee (BPHTB). The tax burden listed does not include other costs such as the cost of charging Non-Tax State Revenue (PNBP) and other costs associated with the transfer of rights which, when accumulated, tend to burden the landowner. The formulation of the problem discussed in this study is how the legal certainty of income tax imposition on sale and purchase transactions of uncertified land in Indonesia uses a normative juridical approach method to solve problems by examining secondary data in the form of laws and regulations, books, and related documents. The results of the study state that the imposition of final income tax on the transfer of rights to land and buildings (PPh F PHTB) that have not been certified or registration of certificates for the first time is considered not to fulfill aspects of legal certainty and justice. This is because there will be the imposition of Final Income Tax on the Transfer of Rights on Land and Building (PPh F PHTB) in layers on the same object and tax subject.